Dexamethasone suppresses the proliferation and migration of VSMCs by FAK in high glucose conditions - Ali Akbar Soleimani; Asghar Mohammadi; Ghasem Ghasempour; Borhan Rahimi Abkenar; Nafiseh Shokri; Mohammad Najafi (BMC Pharmacology and Toxicology, 2022)
Abstract Background High glucose conditions cause some changes in the vessels of diabetes through the signal transduction pathways. Dexamethasone and other corticosteroids have a wide range of biological effects in immunological events. In the present study, the effects of dexamethasone were investigated on the VSMC (vascular smooth muscle cell) proliferation, and migration based on the FAK gene and protein changes in high glucose conditions. Methods and materials The vascular smooth muscle cells were cultured in DMEM and were treated with dexamethasone (10–7 M, 10–6 M, and 10–5 M) for 24, and 48 h in high glucose conditions. The cell viability was estimated by MTT method. The FAK gene expression levels and pFAK protein values were determined by RT-qPCR and western blotting techniques, respectively. A scratch assay was used to evaluate cellular migration. Results The FAK gene expression levels decreased significantly dependent on dexamethasone doses at 24 and 48 h. The pFAK protein values decreased significantly with a time lag at 24- and 48-h periods as compared with gene expression levels. Conclusion The results showed that the inhibition of VSMC proliferation and migration by dexamethasone in the high glucose conditions may be related to the changes of FAK.